Level 1 Level 3
Level 2

ТРИГОНОМЕТРІЯ


31 words 0 ignored

Ready to learn       Ready to review

Ignore words

Check the boxes below to ignore/unignore words, then click save at the bottom. Ignored words will never appear in any learning session.

All None

Ignore?
Синус (А+-В)=
сінусА × косинусВ +- косинусА × сінус В
Косинус (А+-В)=
косинусА × косинусВ -+ сінусА × сінус В
Тангенс (А+-В)=
(тангенсА +- тангенсВ) / (1 -+ тангенсА × тангенсВ)
Котангенс (А+-В)=
(котангенсА × котангенсВ -+ 1) / (котангенсА +- котангенсВ)
СінусА + СінусВ=
2сінус(А+В)/2 × (косинус(А - В)/2)
СінусА - СінусВ=
2косінус(А+В)/2 × (синус(А - В)/2)
КосинусА + КосинусВ=
2косінус((А+В)/2) × (косинус(А - В)/2)
КосинусА - КосинусВ=
-2сінус(А+В)/2 × (синус(А - В)/2)
ТангенсА +- ТангенсВ=
(сінус(А +- В)) / (косинусА × косінусВ)
КотангенсА +- КотангенсВ=
сінус(В+-А) / (сінусА×СінусВ)
Сінус2а=
2сінусА × косинусА
Косинус2а=
2косинусквадратА - 1
Тангенс2а=
(2тангенсА) / (1 - тангенсквадратА)
Косинус2а=
Косинусквадрат А - синусквадратА
Косинус2а=
1 - 2сінусквадратА
Котангенс2а=
(котангенсквадратА - 1) / (2котангенсА)
СінусА=
(2тангенс × (А/2)) / (1 + тангенсквадрат(А/2))
ТангенсА=
(2Тангенс(А/2) / (1 - тангенсквадрат(А/2)
КосинусА=
(1 -тангенсквадрат(А/2)) / (1+тангенсквадрат(А/2))
КотангенсА=
(1 -тангенсквадрат(А/2)) / (2тангенс(А/2))
Сінус(А/2)=
+- КОРІНЬ(1 - косінусА)\2
Тангенс(А/2)=
+- КОРІНЬ(1 - косинусА) / (1+косинусА)
Котангенс(А/2)=
+-КОРІНЬ(1+косинусА) / (1 - косинусА)
Косинус(А/2)=
+- КОРІНЬ(1+косинусА) / 2
Тангенс(А/2)=
(сінусА) / (1+косинусА) = (1-косинусА) / (сінусА)
Котангенс (А/2)=
(сінусА) / (1-косінусА) = (1+косинусА) / синусА
СінусквадратА=
(1-косинус2а) / 2
КосинусквадратА=
(1+косинус2А)/2
СинусА × СінусВ=
(косинус(А - В))_ - косинус(А+В)) / 2
КосинусА × КосинусВ=
(косинус(А - В)) + косинус(А+В)) / 2
СинусА × КосинусА=
(синус(А - В)) + синус(А+В)) / 2